Development of explicit criteria identifying potentially inappropriate polypharmacy in older adults in New Zealand primary care: a mixed-methods study - Jeff Harrison; Lisheng Liu (CSIRO Publishing, 2023)
Introduction The link between polypharmacy, risk of potentially inappropriate medication exposure, and avoidable medicines-related harm is well recognised. Not all polypharmacy is harmful, and contemporary multimodal approaches to managing long-term conditions are evidence-based and commonplace. What is needed is a focus on reducing inappropriate medication prescribing in polypharmacy. Aim This study aims to develop the New Zealand criteria, a set of New Zealand-specific potentially inappropriate medication indicators to correct for older adults with polypharmacy. Methods A mixed-methods approach was used. An expert panel group comprising four clinical pharmacists, two general practitioners, one geriatrician, and two nurse practitioners generated a collection of ideas via the nominal group technique, which combined with published criteria from literature, provided the list of potential criteria. These potential criteria were reviewed, validated, and ranked for importance via a two-round modified Delphi analysis with the same panel. Results The nominal group technique generated 35 indicators, of which 23 were rated as important. Fifty-nine of 91 indicators from literature were rated as relevant and important. This generated 82 indicators for the modified Delphi analysis, from which 61 achieved consensus. Overall, 21 unique criteria were judged 'very important', 31 were judged 'important', and nine were judged 'somewhat important'. No indicators were judged 'low importance'. Discussion The New Zealand criteria provides 61 medication indicators, which New Zealand experts recommend should prompt formal, documented review. The criteria can be used to systematically identify patients at the highest risk of avoidable medication-related harm for proactive review.